Australian energy policy: shortfalls and roadblocks for sustainable change. Issue 4 (2nd October 2017) - Pearce, Prafula
Abstract: As a result of the principles laid down by the global community, there is a growth occurring in renewable energy. However, there is a lack of Australian Government policy to preserve fossil fuels, in particular, oil and gas in Australia. The Australian government is not keeping up with the changes that are occurring in the market place and with the current and future needs of the Australian society. This is having an impact on the community and businesses. This paper explores three case studies that indicate the impact on businesses and the Australian community due to the lack of comprehensive federal Australian Energy Policy. The three case studies explored are: The South Australian Electricity Crisis; The status of Australia's gas resource and the regulatory regime; and Australia's national strategy for the Conservation of oil. The paper concludes that the Australian Government should not wait for crises to occur whereby businesses and the community suffer before implementing appropriate policies. Pro-active policies can assist in a smooth and painless transition to a reduction in fossil fuel use, the preservation of fossil fuels for future generations and an increase in the use of renewable energy.